When venture capitalists are attracted by the experienced - Dohyeon Kim; Su Yong Lee (Journal of Innovation and Entrepreneurship, 2022)
This article tries to find when the experience plays a key role in investment decisions by venture capitalists (VCs) investment decisions. First, we analyze the relative importance of the decision-making criteria that VCs have in mind. Then, the relationship between uncertainty and entrepreneurs' experience is investigated. The conjoint analysis and the multiple regression analysis model are applied to sets of hypothetical scenarios to assess the relative importance of the decision-making criteria of the 263 South Korean VCs. VCs generally value entrepreneurs' education and industry experience in making the investment decision. However, when uncertainty is very high, the newness of the product is high and the completeness of the product is low, VCs focus on entrepreneurs' managerial experience of entrepreneurs. These findings indicate that environmental uncertainty changes the relative importance of the VC investment criteria. Our research enhances the understanding of how VCs chose to invest, thus helping start-up companies receive VC funding and, ultimately, fostering the growth of high-risk-high-return companies.
Keywords: 650; Entrepreneurial experience; Managerial experience; Uncertainty; Venture capital investment